Durability of high performance Ni–yttria stabilized zirconia supported solid oxide electrolysis cells at high current density - Hjalmarsson, Per; Sun, Xiufu; Liu, Yi-Lin; Chen, Ming (Journal of power sources, 2014)
We report the durability of a solid oxide electrolysis cell (SOEC) with a record low initial area specific resistance (ASR) and a record low degradation rate. The cell consists of a Ni-yttria stabilized zirconia (YSZ) cermet as support and active fuel electrode, a YSZ electrolyte, a gadolinia doped ceria (CGO) inter-diffusion barrier, and a strontium doped lanthanum cobaltite (LSC)-CGO composite oxygen electrode. The cell was tested at 800[degrees]C and -1 A cm super(-2) converting 31% of a 0.1:0.45:0.45 mixture of H sub(2):H sub(2)O:CO sub(2 ) for approximately 2700 h, demonstrating an initial ASR of 200 m[Omega] cm super(2) and a steady degradation rate of [< or =]12 mV (or 0.9%) per 1000 h. Electrochemical impedance spectroscopy (EIS) was used to study in situ changes in the electrochemical response of the cell and the retrieved data was treated to deconvolute resistive contributions from the physiochemical processes occurring within the cell. The results showed rapid initial fuel electrode degradation during the first 350 h followed by partial reactivation. The serial resistance was found to increase with time but in an exponentially decaying behavior. A discussion is made based on the detailed electrochemical results together with post-mortem microstructural analysis.